Extraction of the key infrared radiation temperature features concerning stress and crack evolution of loaded rocks - Wei Liu; Liqiang Ma; Michel Jaboyedoff; Marc-Henri Derron; Qiangqiang Gao; Fengchang Bu; Hai Sun (International Journal of Mining Science and Technology)
The infrared radiation temperature (IRT) variation concerning stress and crack evolution of rocks is a critical focus in rock mechanics domain and engineering disaster warning. In this paper, a methodology to extract the key IRT features related to stress and crack evolution of loaded rocks is proposed. Specifically, the wavelet denoising and reconstruction in thermal image sequence (WDRTIS) method is employed to eliminate temporal noise in thermal image sequences. Subsequently, the adaptive partition temperature drift correction (APTDC) method is introduced to alleviate temperature drift. On this basis, the spatial noise correction method based on threshold segmentation and adaptive median filtering (OTSU-AMF) is proposed to extract the key IRT features associated with microcracks of loaded rocks. Following temperature drift correction, IRT provides an estimation of the thermoelastic factor in rocks, typically around 5.29×10−5 MPa−1 for sandstones. Results reveal that the high-temperature concentrated region in cumulative thermal images of crack evolution (TICE) can elucidate the spatiotemporal evolution of localized damage. Additionally, heat dissipation of crack evolution (HDCE) acquired from TICE quantifies the progressive failure process of rocks. The proposed methodology enhances the reliability of IRT monitoring results and provides an innovative approach for conducting research in rock mechanics and monitoring engineering disasters.